Simulasi Efek Jumlah Event Terhadap Respon Energi TLD LiF: Mg, Cu, P - Wahmisari Priharti (JURNAL INFOTEL, 2020)
The effect of different number of events on the bare thermoluminescent dosimeter (TLD) LiF:Mg,Cu,P chip energy response has been simulated using Geant4. This simulation aims to determine the optimum number of events with a minimum computational time. 14 photon energies in a range of 16–1250 keV with a range number of events 2×107 – 2×1012 were applied. A LiF: Mg, Cu, P chip with 4.5 mm diameter and 0.9 mm thick on the surface of 30×30 cm2 water phantom and a thin 10 µm slice of water (at 10 mm deep in the phantom) were considered as the sensitive volumes to calculate the respective absorbed dose DTLD and DW. The relative energy response R was calculated from the ratio of DTLD and DW for each energy normalised to DTLD and DW ratio of energy 662 keV. 2×109 number of events were found to be the optimum number of events with a minimum computational time.The simulation results were validated to the measurement results and the mean deviation of 0,59% was yielded. As the deviation are within the acceptable limit of ±25%, it was concluded that the results were considered satisfactory and the materials and physics processes applied in the code were correct.